Transcaval Valve-in-Valve-in-Valve Aortic Valve Replacement for Bioprosthetic Valve Degeneration. Issue 2 (March 2018) - Watkins, A. Claire; Devireddy, Chandan M.; Al-Atassi, Talal; Simone, Amy E.; Forcillo, Jessica; Thourani, Vinod H.
A 74-year-old man presented with progressive dyspnea on exertion. History included peripheral arterial disease and coronary artery bypass grafting with aortic valve replacement 12 years ago. Subsequently, the surgical valve developed severe stenosis and moderate insufficiency. He underwent a transapical valve-in-valve transcatheter aortic valve replacement 5 years before presentation. This second valve developed a mean gradient of 66 mm Hg with mild insufficiency. The patient was treated with a third aortic valve using an alternative transcaval approach, significantly alleviating his symptoms.